Ecosystem health appears neglected in the management of the human-macaque interface: A systematic review - Sukuman Rittem; Tithipong Plangsangmas; Simon R. Ruegg (One Health)
Macaques (Macaca spp.) are reported in human-wildlife interaction in anthropogenic areas. The management of human-macaque interactions (HMI) requires an understanding of various perspectives and knowledge. One Health (OH) is a transdisciplinary approach to address the well-being and health of animals, humans, and ecosystems, which supports sustainable management through its three pillars: economy, ecology, and society. Thus, the OH approach could be applied to HMI management. To explore the HMI management within the context of the OH approach, we examined articles related to the management of HMI from 2013 to 2022 following the systematic review by PRISMA guidelines. Ninety-four publications were included in the study. Then, we extracted information on HMI framing, management activities, species, and location and categorized HMI framings and management activities into themes of three OH domains and three pillars of sustainability. We noticed an underrepresentation of the society and economy pillars in HMI management and the ecosystem health domain was the least explored in both the HMI and management activities. When we connected publications addressing all three pillars with OH domains in management activities, the number focused on ecosystem health (3/13) remained limited. The most frequently reported HMI theme was “crop feeding”(n=42) and management activities were “HMI management” (n=42). Most publications lacked any form of evaluation of the HMI management. The challenges to better consider ecosystem health in the HMI and to promote participatory governance present an opportunity to apply the OH approach in wildlife conservation and management.